2021
DOI: 10.1002/ajpa.24250
|View full text |Cite
|
Sign up to set email alerts
|

Adapting in the Arctic: Habitual activity and landscape interaction in Late Holocene hunter‐gatherers from Alaska

Abstract: Objectives This study compares lower limb diaphyseal robusticity between Native Alaskan hunter‐gatherers to reconstruct patterns of mobility and engagement with terrain. Materials and methods Ancestral remains included in this study date between 600 and 1800 C.E. and were divided into three regions: Coastal Bay, Far North Coastal, and Inland/Riverine. Cross‐sectional properties were determined at femoral and tibial midshafts and standardized by powers of body mass and bone length. Results Consistently elaevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 75 publications
3
21
0
Order By: Relevance
“…Humeri and lower limb robusticity values are most similar to, and even surpass, values in groups with intense activity in oceanic marine and terrestrial mountainous environments. These results support previous research that found high levels of femoral and tibial robusticity in non-industrialized individuals who inhabit rugged environments (Stock and Pfieffer, 2004;Temple et al, 2021;Ruff, 1999;Marchi, 2008), and high levels of humeral robusticity in marine-hunter-gatherers who heavily rely on diverse oceanic resources (Stock and Pfeiffer, 2001;Stock, 2006;Temple et al, 2021;Weiss, 2003). Further, these results indicate that despite marine-hunter-gatherers having a localized food resource, similar to sedentary agricultural groups, high levels of mobility are required in desert ecologies potentially from the need to travel between freshwater springs and subsistence resources.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Humeri and lower limb robusticity values are most similar to, and even surpass, values in groups with intense activity in oceanic marine and terrestrial mountainous environments. These results support previous research that found high levels of femoral and tibial robusticity in non-industrialized individuals who inhabit rugged environments (Stock and Pfieffer, 2004;Temple et al, 2021;Ruff, 1999;Marchi, 2008), and high levels of humeral robusticity in marine-hunter-gatherers who heavily rely on diverse oceanic resources (Stock and Pfeiffer, 2001;Stock, 2006;Temple et al, 2021;Weiss, 2003). Further, these results indicate that despite marine-hunter-gatherers having a localized food resource, similar to sedentary agricultural groups, high levels of mobility are required in desert ecologies potentially from the need to travel between freshwater springs and subsistence resources.…”
Section: Discussionsupporting
confidence: 91%
“…To make inferences on the types and intensity of activity of individuals from the Cape Region and Central Desert Sierras, cross-sectional geometric properties of the humerus, femur, and tibia were compared to a diverse sample of non-industrial humans who differed in behaviors (marine-hunter-gatherers to agriculturalists) and terrain (Table 1). Alaska North Coast, Alaska Coast, and Andaman Island samples represent individuals with high levels of maritime adaptations with varying degrees of marine hunting, watercraft use, swimming, and shellfish gathering (Table 1; Stock and Pfeiffer, 2001;Stock, 2006;Temple et al, 2021). Alaska Coast and Andaman Island are of individuals with low levels of terrestrial mobility in relatively flatter terrain, while Alaska North…”
Section: Comparative Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…While these evolutionary studies clearly demonstrate a general decrease or changes in skeletal robusticity over time correlated with subsistence mobility or technological innovation, without sufficient sample sizes and wider range of age distributions, they are not able to detect or make meaningful interpretations of age‐ or sex‐related bone loss. However, recent comparative studies of cortical long bone robusticity in a variety of modern populations have found varying patterns of sexual dimorphism that have been suggested to reflect differences in gendered activities and behavior (Laffranchi et al, 2020; Saers et al, 2017; Temple et al, 2021; Zelazny et al, 2021). While these studies do not consider age‐related changes and/or do not have sufficient sample sizes to do so, they do underscore the plasticity of bone morphology with behavior/lifestyle and do not support the “mismatch” hypothesis that females in modern human populations are predestined to have less robust bones or bone fragility.…”
Section: Variation and Plasticity: The Archeological Perspectivementioning
confidence: 99%